The Effect Of Multy Reprecentacy Discourse Learning Assisted By Liveworksheet On Students' Mathematical Comprehension Ability - hamidah; Wijaya kusuma, Jaka; Ainni, Irma (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2024)
The discourse multy reprecentacy (DMR) model is one of the models that are able to improve students' mathematical understanding by collaborating in groups in class and using the Liveworksheet application. This study aims to determine the influence of students' mathematical knowledge after verifying the DMR model with the Liveworksheet application. This study uses a quantitative approach. Using a sample of grade VII students at SMPN 1 Cikeusik, class VIIA as an experimental class and VIIB as a control class were taken using a purposive sampling technique. The data collection techniques used in this study are observation and tests. This study uses statistical data analysis, but previously, a prerequisite test was carried out to conduct data analysis with parametric statistics using the polled variance formula. Based on the research, it can be concluded that the influence of the DMR model with the Liveworksheet application on the mathematical comprehension ability of junior high school students.  Keywords: Multy Reprecentacy Discourse Model; Liveworksheet app; Understanding Mathematics